Penyesuaian Psikologis Anak dalam Keluarga Pasca Perceraian: Tinjauan Psikologi Keluarga - Muhammad Wahyu Pratama (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Children’s psychological adjustment in post-divorce families is a complex and dynamic process shaped by individual, relational, and contextual factors. This study examines how children adapt psychologically following parental divorce through a family psychology perspective, emphasizing risk factors, protective mechanisms, and psychological interventions. The findings indicate that divorce itself does not automatically lead to maladjustment; rather, ongoing interparental conflict, economic instability, and inconsistent parenting significantly increase children’s vulnerability to emotional and behavioral problems. Conversely, cooperative parenting, stable caregiving arrangements, social support, and evidence-based psychological interventions function as critical protective factors that foster resilience. Family-based interventions, including structured play therapy, counseling, and post-divorce support programs, demonstrate effectiveness in reducing psychological symptoms and enhancing children’s emotional stability. Integrating psychological, social, and normative dimensions, including parental responsibility and child rights, further strengthens long-term adjustment outcomes. Overall, a holistic and evidence-based family psychology approach is essential to support children’s psychological well-being and adaptive development in the context of post-divorce family transitions..